Enhancement of photodegradation efficiency of PVA/TiO2 nanofiber composites via plasma treatment. (September 2020) - Montallana, Arantxa Danielle S.; Lai, Bo-Zhang; Chu, Jinn P.; Vasquez, Magdaleno R.
Abstract: Anatase titanium dioxide (TiO2 ) nanoparticles (NPs) embedded in poly(vinyl alcohol) (PVA) nanofibers were fabricated for the photodegradation of methylene blue (MB) as the test analyte. 1 wt% TiO2 NPs were dispersed in 12 wt% PVA solution prior to electrospinning to form the nanofibers. Raman spectroscopy implied the incorporation of the NPs into the nanofibers without significant change in the chemical structure of either TiO2 or PVA. Scanning electron microscopy, energy dispersive x-ray spectroscopy, and transmission electron microscopy revealed smooth, bead-free, and continuous nanofibers, uniform NP distribution, and negligible NP agglomeration, respectively. The effect of oxygen plasma treatment on the photodegradation efficiency of the PVA/TiO2 was also investigated. Photodegradation of MB exhibited up to 30% increase in degradation efficiency using the plasma-treated PVA/TiO2 nanofiber mats. The partially exposed immobilized TiO2 NPs became more photocatalytically active while being supported by PVA nanofibers. Immobilization of TiO2 NPs would allow reusability thereby extending its service life ideal for environmental applications.